Au NPs fabricated on biguanidine-modified Zr-UiO-66 MOFs: a competent reusable heterogeneous nanocatalyst in the green synthesis of propargylamines. (21st January 2022) - Veisi, Hojat; Sayadi, Marzieh; Morakabati, Neko; Tamoradi, Taiebeh; Karmakar, Bikash
Abstract : In this study, we utilized functionalized metal organic frameworks (MOFs) as a host matrix to embed gold (Au) nanoparticles. Abstract : In this study, we utilized functionalized metal organic frameworks (MOFs) as a host matrix to embed gold (Au) nanoparticles. The three-dimensional Zr-based metal–organic framework UiO-66-NH2 was functionalized with the biguanidine moiety using a post-synthetic modification (PSM) strategy, and then gold salt was successfully immobilized onto the surface of the biguanidine-functionalized Zr-MOF. The morphological and physicochemical features of the material were determined using several advanced techniques like FT-IR spectroscopy, SEM, TEM, EDX spectroscopy, elemental mapping, XRD and ICP-OES. The SEM, BET and XRD results showed that the morphology and structure of the Zr-MOF were retained after multiple transformations. The obtained UiO-66-bigua/Au nanocomposite exhibited excellent activity in the three-component reaction of aldehydes, amines and alkynes (A 3 coupling) with good to high yields of diverse propargylamines. Furthermore, the catalyst could be recovered and reused 8 times with no significant reduction in its activity.